1992
DOI: 10.1136/ard.51.12.1332
|View full text |Cite
|
Sign up to set email alerts
|

Long term prognosis in yersinia arthritis: clinical and serological findings.

Abstract: Twenty two patients were foilowed up for a mean of 10-7 years after acute yersinia arthritis. Their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 11 publications
(2 reference statements)
2
6
0
Order By: Relevance
“…In a previous study with similar length of follow up, we found radiological sacroiliitis in 36% of patients, half of whom had progressive changes 15. In a similar study on yersinia arthritis by Herrlinger and Asmussen,16 5% of patients had developed ankylosing spondylitis, and another 5% had progression of pre-existing ankylosing spondylitis. With extended follow up, the figures may even increase.…”
Section: Discussionsupporting
confidence: 60%
“…In a previous study with similar length of follow up, we found radiological sacroiliitis in 36% of patients, half of whom had progressive changes 15. In a similar study on yersinia arthritis by Herrlinger and Asmussen,16 5% of patients had developed ankylosing spondylitis, and another 5% had progression of pre-existing ankylosing spondylitis. With extended follow up, the figures may even increase.…”
Section: Discussionsupporting
confidence: 60%
“…We believe the different patterns of disease are not related to the primate species or subspecies, but rather to the infecting organism. Similar patterns of disease have been demonstrated in humans (Table II) [Ahvonen et al, 1969;Bardin & Lathrop, 1992;Bengtsson et al, 1983;Borg et al, 1992;Buxton et al, 2002;Calin & Fries, 1976;Cheevers and McGuire, 1988;Cohen et al, 1987;Cole et al, 1970;Deighton, 1993; Ahvonen et al [1969]; Bardin and Lathrop [1992]; Borg et al [1992]; Buxton et al [2002]; Calin and Fries [1976]; Cohen et al [1987]; Deighton [1993]; Dworkin et al [2001]; Graham [1919]; Hannu and Leirisalo-Repo [1988]; Hannu et al [2002]; Herrlinger and Asmussen [1992]; Hughes et al [1991]; Kanakoudi-Tsakalidous et al [1998]; Kvien et al [1994]; Laasila and Leirisalo-Repo [1999]; Leino et al [1980]; Leirisalo-Repo et al [1997]; ; Locht et al [1993; Maki-Ikola and Granfors [1992]; Maximov et al [1992]; Merilahti-Palo et al [1991]; Putterman and Rubinow [1993]; Rudwaleit et al [2001]; Simon et al [1981]; Solitar et al [1998]; Stein et al [1980];…”
Section: Habitat and Microorganismssupporting
confidence: 57%
“…In genetically-predisposed individuals, this phenomenon, which is a subclass of spondyloarthropathy, frequently complicates genital infections and infectious-agent diarrhea. Chlamydia and perhaps Mycoplasma have been implicated for the former, while Shigella, Salmonella, Yersinia, Campylobacter, and enteropathic Escherichia coli have been implicated for the latter in humans and other primates [Ahvonen et al, 1969;Bardin & Lathrop, 1992;Bengtsson et al, 1983;Borg et al, 1992;Buxton et al, 2002;Calin & Fries, 1976;Cheevers and McGuire, 1988;Cohen et al, 1987;Cole et al, 1970;Deighton, 1993;Dworkin et al, 2001;Graham, 1919;Granfors et al, 1988;Hannu & Leirisalo-Repo, 1988;Hannu et al, 2002;Held & Whitney, 1978;Herrlinger & Asmussen, 1992;Hughes et al, 1991;Kanakoudi-Tsakalidous et al, 1998;Katz, 1989;Kvien et al, 1994;Laasila & Leirisalo-Repo, 1999;Leino et al, 1980;Leirisalo-Repo et al, 1997;Locht et al, 1993Maki-Ikola & Granfors, 1992;Maximov et al, 1992;Merilahti-Palo et al, 1991;Putterman & Rubinow, 1993;Rothschild & Woods, 1993;Rudwaleit et al, 2001;Simon et al, 1981;Snoy et al, 1985;Solitar et al, 1998;Stein et al, 1980;Taccetti et al, 1994;…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the apparently mandatory second position of arginine, position 45 glutamic acid and position 67 cysteine apparently are required [Buxton et al, 1992;Rojo et al, 1993]. The occurrence of spondyloarthropathy depends not only on host susceptibility, but also on external microorganisms (in the form of infectiousagent diarrhea) [Ahvonen et al, 1969;Bardin & Lathrop, 1992;Borg et al, 1992;Buxton et al, 2002;Calin & Fries, 1976;Cohen et al, 1987;Deighton, 1993;Dworkin et al, 2001;Graham, 1919;Hannu & Leirisalo-Repo, 1988;Hannu et al, 2002;Herrlinger & Asmussen, 1992;Hughes et al, 1991;Kanakoudi-Tsakalidous et al, 1998;Kvien et al, 1994;Laasila & Leirisalo-Repo, 1999;Leino et al, 1980;Leirisalo-Repo et al, 1997;Locht et al, 1993Maki-Ikola & Granfors, 1992;Maximov et al, 1992;Merilahti-Palo et al, 1991;Putterman & Rubinow, 1993;Rudwaleit et al, 2001;Simon et al, 1981;Solitar et al, 1998;Stein et al, 1980;Taccetti et al, 1994;Thomson et al, 1994Thomson et al, , 1995Tupchong et al, 1999;Yli-Kerttula et al, 1995]. Of note is the contraction of spondyloarthropathy by 20-30% in individuals who develop Shigella dysentery, if they possess HLA-B27.…”
Section: Frequency Of Arthritis and Pathophysiology Of Spondyloarthritismentioning
confidence: 99%